Effects of land use and rainfall on sequestration of veterinary antibiotics in soils at the hillslope scale - Zhao, Fangkai; Chen, Liding; Yang, Lei; Sun, Long; Li, Shoujuan; Li, Min; Feng, Qingyu (Environmental pollution (1987), 2020)
Veterinary antibiotics have been detected as contaminants of emerging concern in soil environment worldwide. Animal manure is frequently applied to agricultural fields to improve soil fertility, which can result in introducing large amount of antibiotics into soil environment. However, few attempts have been made to identify the spatial and temporal dynamics of veterinary antibiotics in soil at the hillslope scale with different land uses. This study was performed to explore the pattern and variability of veterinary antibiotics in the soil in response to rainfall events. Results showed that higher concentrations of veterinary antibiotics were generally found in cropland (292.6 ± 280.1 ng/g) and orchard (228.1 ± 230.5 ng/g) than in forestland (13.5 ± 9.9 ng/g). After rainfall events, antibiotics accumulated in the soil at the positions where manure was applied, especially under high-intensity rainfall conditions. However, the antibiotic concentration in soil slightly increased from the top to the bottom of hills, thus indicating the restricted contribution of runoff to antibiotic transport, especially under low-intensity rainfall conditions. In addition, most antibiotics were sequestered in the surface soil (0–10 cm), and higher antibiotic concentrations were observed in deep soil (20–40 cm) in cropland than orchard. The soil aggregate, organic matter, and clay content played important roles in antibiotic sequestration along the hillslope subject to low-, medium-, and large-amount rainfall events, respectively. This study identified that land use, rainfall conditions, and soil structures jointly affect the spatial and temporal variability of antibiotics in soils on hillslopes. [Display omitted] •Spatial variability of antibiotics in soil was demonstrated at the hillslope scale.•Antibiotics accumulated in the soil at the manure-amended hillslope positions.•Rainfall characteristics affected persistence of antibiotics in hillslope soil.•Soil structure modified by rainfall events correlated with variability of antibiotics.